Adding Plasticizer Dispersible Conducting Polymer to the Ion‐selective Membrane Composition – Revitalizing Single Piece Ion‐selective Electrodes Concept. Issue 3 (12th August 2022) - Jaworska, Ewa; Maksymiuk, Krzysztof; Michalska, Agata
Abstract: Typically, ion‐selective electrodes used in current triggered electrochemical sensing apply a conducting polymer layer covered with an ion‐selective membrane. In this work we propose an ion‐selective membrane containing a dispersed conducting polymer. Thus obtained system allows elimination of the Achilles hell of heterogeneous ion‐selective membranes containing solid particulates dispersed within the ion‐selective polymeric membrane. The herein proposed system, even for high conducting polymer loading equal to 5 % w/w, is characterized with insensitivity towards redox interferences, as well as potentiometric detection limits, selectivity well comparable with that for other ion‐selective electrodes constructions. Under voltammetric conditions, with increasing loading of the conducting polymer in the membrane cathodic peak potentials are shifted towards more negative values, yet the linear dependence of the peak potential on logarithm of concentration of the analyte in the solution is preserved. Abstract :